Co-Creation of Value through Customer Experience: A Case Study of UK Watch Brand Storm - Wu, YanYan (2010)
The service dominant logic, which supposed that value should be created by customer during their interactions with firm and embedded in experience, posed a great challenge to the traditional marketing paradigm that assumed that value is created by sellers and embedded in the product output. In addition, with the changing role of customer, marketing focus has shifted from the firm centric to customer centric. Firms cannot manipulate the value creation process unilaterally, instead, it is advisable that customers should always be regarded as the co-creator of value and engaged in the value creation process. On the other hand, the advanced technological development and prevalence of internet facilitated the co-creation of value process. The aim of this dissertation is going to explore the essence of the co-creation of value with customer through customer experience, and how the process works based on DART model in the real business world. A qualitative research was conducted based on a UK watch brand.